Anticipating control over aversive stimuli is mediated by the medial prefrontal cortex: An fMRI study with healthy adults. Issue 13 (9th June 2021) - Wade‐Bohleber, Laura Maria; Haugg, Amelie; Huber, Sabrina; Ernst, Jutta; Grimm, Simone; Recher, Dominique; Richter, Andre; Seifritz, Erich; Boeker, Heinz; Northoff, Georg
Abstract: The anticipation of control over aversive events in life is relevant for our mental health. Insights on the underlying neural mechanisms remain limited. We developed a new functional magnetic resonance imaging (fMRI) task that uses auditory stimuli to explore the neural correlates of (1) the anticipation of control over aversion and (2) the processing of aversion. In a sample of 25 healthy adults, we observed increased neural activation in the medial prefrontal cortex (ventromedial prefrontal cortex and rostral anterior cingulate cortex), other brain areas relevant for reward anticipation (ventral striatum, brainstem [ventral tegmental area], midcingulate cortex), and the posterior cingulate cortex when they anticipated control over aversion compared with anticipating no control (1). The processing of aversive sounds compared to neutral sounds (2) was associated with increased neural activation in the bilateral posterior insula. Our findings provide evidence for the important role of medial prefrontal regions in control anticipation and highlight the relevance of conceiving the neural mechanisms involved within a reward‐based framework. Abstract : The anticipation of control over aversive events in life is relevant for our mental health. In healthy adults, control anticipation over aversive sounds is associated with increased neural activation in the medial prefrontal cortex and other brain areas relevant for reward anticipation.